The Implementation of RADEC Model Assisted by Crossword Puzzle to Improve Students’ Critical and Creative Thinking - Azizah, Zhazha Lutfi; Dayati, Umi; Hady , Nuruddin (Edukasi, 2024)
Critical and creative thinking abilities of 8th-grade students in MTs Ahmad Yani Jabung Malang are still low. This can be seen when students have difficulties in expressing opinions and finding a correlation between materials and problems in the student environment. Students are also not creative in making alternative answers to problems because most students answer by copying answers from the 8th-grade civic education book. This study aims to determine the implementation of the RADEC learning model assisted by Crossword Puzzles to improve students' critical and creative thinking abilities. This study used a qualitative approach. The type of study used was classroom action research, which was conducted in two cycles. Each cycle consisted of three stages: (1) planning, (2) action or observation, and (3) reflection. The subjects of the study were 26 students in class 8A of MTs Ahmad Yani Jabung. Data analysis included the analysis of learning implementation, critical, and creative thinking. The results of the study showed: 1) the implementation of the RADEC learning model assisted by crossword puzzle showed that there is an improvement in critical thinking ability school of class 8A students in MTs Ahmad Yani Jabung Malang with score gain includes in moderate category, and 2) the implementation of RADEC learning model assisted by Crossword Puzzle showed that there is an improve in creative thinking ability school of class 8A students in MTs Ahmad Yani Jabung Malang with score gain includes in moderate category.